Fortuitous meetings and failures in meeting: the mimic epigrams of Palatina Anthology 5 - Silva, Luiz Carlos André Mangia (ITINERÁRIOS – Revue de Littérature, 2010)
This paper makes use of dramatic studies concepts formulated by Aristotle’s Poetics in order to demonstrate the mimetic nature of a group of Greek epigrams, due to the emphasis the characters (éthe) and the virtual construction of stage performances (ópsis) are given.